EFEKTIVITAS VIDEO ANIMASI MATERI LAPISAN BUMI PADA SISWA KELAS VII DALAM PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Asri Mardhiyyah Wulandari; Laily Rosdiana (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This research aimed to determine the effectiveness of video animations on the earth's layer material for students in online learning during the Covid-19 pandemic on student learning outcomes in science subjects. The subjects in this study were class VII B from SMPN 33 Surabaya and involved 38 students in the Even Semester in the 2020/2021 School Year. This research used the one group pretest-posttest design. This research used descriptive analysis and different tests. The results of this research indicated that the animation video of the earth's layer effectively improved science learning outcomes for class VII B students of SMPN 33 Surabaya. This can be seen through the results of the pretest and posttest which showed an increase in the average value of student learning outcomes and the different tests which showed that there was a difference between before and after the use of animated videos of the earth's layers.